The Psychosocial Trauma of ACL Ruptures in Young Athletes. Issue 7 (21st July 2017) - Padaki, Ajay Shridar; Popkin, Charles Aaron; Noticewala, Manish Suresh; Ahmad, Christopher S.
Objectives: Sustaining severe injuries requiring operative fixation causes emotional harm in addition to physical damage in young athletes. While the fear of re-injury following an anterior cruciate ligament ruptures and reconstruction has been established, the extent of the psychosocial trauma, including hyperarousal and intrusion, is largely unknown. We hypothesize that post-traumatic stress disorder symptoms are present young athletes with strong athletic identities following ACL ruptures. Methods: The impact of events scale, the athletic identity measurement score, and a novel specialization instrument were administered to 7 to 21 year old patients following ACL rupture. These instruments represent a modified post-traumatic stress disorder screening tool psychometrically validated in children, a validated tool to measure athletic identity, and an athlete specialization questionnaire designed by the authors respectively. Athletes were recruited from the sports medicine clinic at the senior authors' academic institution and the instruments were administered upon the patients' first orthopedic visit following the diagnosis of an ACL rupture. The full extent of the knee injury and any history of prior knee injuries were also assessed. Results: Twenty-one patients with a mean age of 14.9 ± 2.9 years completed the emotional trauma assessment and 52.2% of respondents were female. The most common concurrent injury was a meniscal tear (47.8%) and 9.5% of patients reported a prior ACL rupture and reconstruction. Regarding specialization, one-third of athletes played one sport only, 52.4% of athletes played multiple sports while focusing on one above the others, and 14.2% of athletes balanced their sports equally. Single-sport athletes scored significantly higher on the athletic identity questionnaire (single-sport mean 57.2; multi-sport mean 52.1; p = .02). The majority of patients experience traumatic symptoms in all three major categories as 86.4% endorsed avoidance symptoms, 81.8% admitted intrusion symptoms, and 81.8% admitted hyperarousal symptoms. Older athletes were significantly more likely to experience stronger emotionally traumatic symptoms (p = .03) as 16 - 21 year old athletes scored a mean of 62.6 on the Impact of Events Scale compared to 39.6 for 7 - 15 year old athletes. While male patients experienced stronger traumatic symptoms than female patients, the separation was not found to be statistically significant (male 50.2; female 43.6; p = .12). Conclusion: The emotional trauma for young athletes following ACL ruptures extends beyond the avoidance symptoms that have been previously established. Psychological evaluation and support is imperative to providing holistic care following this injury. Demographics and Psychosocial Symptom Prevalence Age 14.9 ± 2.9 Female 52.8% Male 47.2% Meniscal Injury 47.2% Prior ACL Injury 9.5% Traumatic Symptoms: Avoidance 86.4% Intrusion 81.8% Hyperarousal 81.8%